Enfoques teóricos sobre la participación educativa en la vejez - Martín García, Antonio Víctor (Teoría de la Educación. Revista Interuniversitaria, 2009)
The purpose of this article is to examine and to estract of différents approaches and theoretical models about aging process, the more important outcomes for educative practice with regard to the educative participation of the older adults. The perspectives of différents approach such as biologic and behavioral perspective; Lifespan model; Disengagement theory; Activity theory; Subcultural theory; and Continuity theory are studied. Finally, the new gerontologies approaches concerning with relativization of the influence on educative participation factors age-asociated are discussed.